'A Nation on the Move': The Indian Constitution, Life Writing and Cosmopolitanism. Issue 2 (2nd April 2016) - Majeed, Javed
ABSTRACT: The Indian Constitution (IC) has been considered in terms of its intertextuality with preceding colonial documents such as the Government of India Act 1935. This essay relocates the IC in intertextual relationships with anti-colonial autobiographies and texts such as Gandhi's Hind Swaraj, showing the parallels between the way they dramatise self-rule and mix global, Indian and regional levels of identity. Both the IC and these texts are marked by processes of transnational and internal dialogue, and reflect transnational aspects of Indian print culture and the subject positions it gave rise to. Widening the discursive sites of the IC to include anti-colonial autobiographies raises questions about the IC as a species of autobiography itself, and it also gives us another perspective on the tensions within the IC, showing how the conflict between liberty and power is manifested in its linguistic cosmopolitanism and its approach to translation. Constitutions embody the aspirations of a nation's citizens, and the IC's verbal skills grade and structure these aspirations, plotting them along a spectrum of possible futures and grounding them in a variety of pasts. This concern with temporality has a parallel in some anti-colonial autobiographies where the consciousness of time is particularly acute. Finally, both the IC and Indian anti-colonial life writing can be seen as instances of South Asian literary modernity in terms of the style of their creative choices.